(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Epithelial ovarian cancer is the eighth most common malignancy in women, with the highest mortality rates regardless of significant advances in therapeutic techniques This is due to the fact that the symptoms of epithelial ovarian tumors are vague and nonspecific, concealing the disease's early onset and progression. Several immunological markers, including CA125, AFP, Inhibin, and B7-H4, have been identified to aid in the diagnosis of epithelial ovarian tumors. The expression of the novel biomarker B7-H4 in epithelial ovarian tumors tissues is investigated in this study. We also investigated the link between B7-H4 expression and biological behaviour as well as risk factors. Methodology This cross-sectional study validated the diagnosis of epithelial ovarian tumours and histological characterization by examining morphological features. B7-H4 expression was examined immunohistochemically in the most representative tumour block. Mean frequency and percentages were calculated for quantitative variables, The chi-square test and Fisher's Exact Test were used to examine qualitative variables, and P values less than 0.05 were considered significant.. Results IHC expression was found to be positive in 50 of 66 cases (75.7%). The majority of patients with B7-H4 IHC positivity have benign epithelial ovarian tumours (25/50; 50%), followed by malignant (19/50; 38%) and borderline (6/50; 12.5%) tumours. This demonstrates a statistically significant (p=0.004) link between B7-H4 and epithelial ovarian tumours. Furthermore, epithelial ovarian tumours with distinct morphology, such as Brenner tumours of the ovary, were discovered to express the B7-H4 protein 2/2. Statistics show a link between B7-H4 protein expression and these unusual mutations. On a scale of one to four, the majority of the positive samples had a protein expression strength of one, with a statistically significant estimate. Conclusion B7-H4 expression has been linked to epithelial ovarian tumours, and it is expected to emerge as a new molecular marker to assess the biological activity of these tumours. Other members of the B7 family, such as B7-H3, B7-H5, B7-H6, and B7-H7, may be able to shed more light on tumour immune evasion and aid researchers in the identification of new immunotherapeutic targets for the treatment of ovarian and other cancers.